Emission measurements of biogenic volatile organic compounds in multiple scales - Haapanala, Sami (Helsingin yliopisto, 2012)
Volatile organic compounds (VOCs) are reactive trace gases abundant in the atmosphere. As strongly reactive constituents they have many impacts on the atmospheric chemistry. To properly understand the processes involved in VOC cycles within the biosphere and atmosphere, we must have comprehensive knowledge on the biogenic and anthropogenic emissions and atmospheric concentrations. In this thesis, the emissions of VOCs were measured in many scales from various Fennoscandian ecosystems, utilizing several methods. First, enclosure method was applied to study the branch scale VOC emission from mountain birch. The measurements were conducted during two successive growing seasons. Significant emissions of sesquiterpenes were observed in the first year but not in the second one. Second, relaxed eddy accumulation (REA) method was used to study the ecosystem scale emissions of light hydrocarbons from a wetland. In addition to methane, the only significant emission was that of isoprene. Isoprene emission potential was found to be about 680 μg m-2 h-1. The REA method was further developed by studying the possible stability dependency of the method. Another ecosystem scale flux measurement method, disjunct eddy accumulation (DEA), was applied to study monoterpene emissions from a timber felling area. The emissions of monoterpenes were very high for a few months after felling, peaking at 5200 μg m−2 h−1. Despite of the short period those emissions seem to be of great importance for the atmospheric VOC burden. Third, profiles of boundary layer concentrations of some biogenic and anthropogenic VOCs were measured using a hot air balloon as a platform. Landscape scale emissions were inferred using the concentration data. Overall, our understanding of the previously poorly known VOC emissions from some Fennoscandian ecosystems was increased. This study highlights the importance to quantify emission hotspots of even marginal ecosystems to get comprehensive understanding for emission inventories and future redictions. The correct ...